2020
DOI: 10.3390/cells9041009
|View full text |Cite
|
Sign up to set email alerts
|

Lack of PCSK6 Increases Flow-Mediated Outward Arterial Remodeling in Mice

Abstract: Proprotein convertases (PCSKs) process matrix metalloproteases and cytokines, but their function in the vasculature is largely unknown. Previously, we demonstrated upregulation of PCSK6 in atherosclerotic plaques from symptomatic patients, localization to smooth muscle cells (SMCs) in the fibrous cap and positive correlations with inflammation, extracellular matrix remodeling and cytokines. Here, we hypothesize that PCSK6 could be involved in flow-mediated vascular remodeling and aim to evaluate its role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In 2020, Rykaczewska et al [18]has identi ed that PCSK6 is associated with carotid intima-medial thickness, is an index for atherosclerosis, and immunohistochemistry con rmed that PCSK6 localize in smooth muscle actin positive cells of the brous cap and the neovascular, PCSK6 is increased after arterial injury in a mice carotid artery balloon injury model, and the levels positively correlate with the level of some in ammatory factors such as PDGFB, MMP2/MMP14. Similarly, another study [19]…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In 2020, Rykaczewska et al [18]has identi ed that PCSK6 is associated with carotid intima-medial thickness, is an index for atherosclerosis, and immunohistochemistry con rmed that PCSK6 localize in smooth muscle actin positive cells of the brous cap and the neovascular, PCSK6 is increased after arterial injury in a mice carotid artery balloon injury model, and the levels positively correlate with the level of some in ammatory factors such as PDGFB, MMP2/MMP14. Similarly, another study [19]…”
Section: Introductionmentioning
confidence: 81%
“…The development of atherosclerosis usually correlates with abnormal proliferation, migration and apoptosis of smooth muscle cells [25]. A recent study showed that PCSK6 gene silencing leads to downregulation of VSMC contractile markers and decreased MMP2 expression, instead, PCSK6 gene overexpression increases VSMC proliferation and migration induced by PDGFB [19]. A previous study [18] suggested that PCSK6 snps was associated with artery intima-media thickness, intimal thickening is considered to be a manifestation of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…24 PCSK6 is a critical mediator of TGF- processing and is crucial for reproduction, embryological development and blood pressure regulation. 25-29 A PCSK6 gene variant has been implicated in the development of hypertension 29 and dysregulated PCSK6 gene expression has been linked to vascular disease, [30][31][32] and cardiac remodeling following myocardial ischemia. 33 These cardiovascular remodeling effects make PCSK6 of particular relevance to IPF, as PCSK6 overexpression can lead to increased collagen I and III deposition, TGF- activation and extracellular matrix formation, 33,34 which are cardinal features of IPF pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured human monocytes and endothelial cells, PCSK6 expression and activity are increased by pro-atherogenic lipid oxidation products [ 129 ]. In Pcsk6 KO mice, compromised vascular remodeling, as indicated by enlarged systolic and diastolic circumferences and reduced contractile SMC markers, is observed in carotid arteries exposed to increased blood flow [ 130 ]. Increased PCSK6 expression is also detected in smooth muscle α-actin (SMA) (an SMC marker) -positive cells in unstable carotid plaques, where inflammation and extracellular matrix degradation are active [ 131 ].…”
Section: Pcsk6 and Cardiovascular Pathophysiologymentioning
confidence: 99%